2022
DOI: 10.1002/cbdv.202200558
|View full text |Cite
|
Sign up to set email alerts
|

Coumarins from Sarcandra glabra (Thunb.) Nakai and Acetylcholinesterase Inhibiting Activity

Abstract: Nine coumarins including a pair of new enantiomers (1a/1b) and seven known compounds (2 -8) were isolated from Sarcandra glabra (Thunb.) Nakai. Among them, compounds 1a and 1b were naturally occurring coumarin-phenylpropanoid conjugate enantiomers. Their structures were identified by NMR and ECD calculations. Compounds 1-8 were tested for acetylcholinesterase (AchE) inhibiting activity. The results of the enzymology experiment showed that compound 3 demonstrated obvious AchE inhibitory activity which showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The acetylcholinesterase inhibitory activities were evaluated using our previously reported method (see the Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…The acetylcholinesterase inhibitory activities were evaluated using our previously reported method (see the Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…Wang et al [ 82 ] reported a new coumarin, 3,5-dihydroxycoumarin-7- O -α-L-rhamnopyranosyl-2H-chromen-2-one ( 247 ), possessing anti-inflammatory properties, from S. glabra . From the stems of S. glabra , Du et al [ 83 ] uncovered the presence of five coumarins, namely, a pair of coumarin-phenylpropanoid enantiomers (7 S ,8 S ) and (7 R ,8 R )-sarcacoumarin ( 250 and 251 ) with promising acetylcholinesterase inhibitory activities, and three known compounds ( 252 – 254 ).…”
Section: Chemical Constituentsmentioning
confidence: 99%
“…Isofraxidin 7- O -β-D-xylopyranosyl(1–3)-α-D-glucopyranoside C 22 H 28 O 14 BuOH 250. (7 S ,8 S )-Sarcacoumarin C 21 H 22 O 9 S. glabra, stems (Sanming, Fujian province) AcOEt [ 83 ] 251. (7 R ,8 R )-Sarcacoumarin C 21 H 22 O 9 252.…”
Section: Chemical Constituentsmentioning
confidence: 99%
See 1 more Smart Citation